Studying the efficacy of some commercial inactivated avian influenza H5 vaccines against the currently circulating highly pathogenic H5N8 virus in broiler chickens in Egypt - Hussein AM; El-Bagoury GF; El-Habbaa AS; Samir A. Nassif (VacciMonitor)
The avian influenza H5N8 virus is a highly pathogenic virus that can cause severe economic losses in poultry species worldwide. In Egypt, highly pathogenic avian influenza virus of subtype H5N8 clade 2.3.4.4b was reported in 2016, and despite vaccination efforts, the virus has become endemic. The current study aims to evaluate the efficacy of some commercial inactivated H5 vaccines from a different lineage against the challenge with HPAI H5N8 virus in broiler chickens, in Egypt. Groups of broilers vaccinated with different inactivated H5 vaccines and unvaccinated controls were challenged with HPAI H5N8 virus. Antibody titer was calculated at the first 3 weeks after vaccination and the viral shedding titer was calculated at 3-, 5-, 7- and 10-days post challenge. Mortality rates were monitored daily during the first 10 days after the challenge to provide an estimate of the protection level. According to our findings, following a challenge with the HPAI H5N8 clade 2.3.4.4b virus, the inactivated vaccines offered varying degrees of efficacy, HI titer and reduction of virus shedding titer, which may be related to variations in the nucleotide sequence identity percentages of the HA genes between the challenge virus and the vaccine seeds. These findings emphasize the need for continual updating of the H5 vaccines applied in Egypt to keep up with the continual mutations that discovered in H5Nx viruses.